(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The aim of the research is to demonstrate the impact of the salary localization service in enhancing banking competitive advantage. In order to achieve this goal, salary localization was chosen as an independent variable and its impact was studied on the dependent variable, which is the competitive advantage. The research problem lies in the fluctuation of the salary localization service from one bank to another and the impact of this on the competitive advantage. The study sample included five private Iraqi banks, namely (the National Bank of Iraq, the International Development Bank, Assyria International Bank, Al Khaleej Commercial Bank, and the Middle East Bank) based on the financial statements and annual reports of the banks for the period from 2017 - 2021. To reach the results, the inductive approach and the descriptive approach were used. Analytical. The research concluded that there is an impact of the localization of salaries in enhancing the banking competitive advantage of the banks in the research sample, and one of the most prominent results of this study is that the banks in the research sample, whose salary localization service contributes to increasing the quality of banking service provided to customers and strengthening the customer’s confidence in dealing with the bank from Through the diversification of its services and keeping pace with the modern development in the banking sector and increasing revenues compared to expenses through electronic services (electronic payment systems and eliminating non-working credit facilities through the salary card by direct deduction and achieving competitive advantage by focusing on customer satisfaction, as customer satisfaction has become a decisive factor in Conditions of Competition in the Modern Business Environment | the introduction. The topic of research helps to achieve the goals of sustainable development the Developed by the unite Nations committees (SDGs) Regarding the economic development of bank.